EXPIRED DRUGS AS INHIBITORS IN ELECTROCHEMICAL PROCESSES – A MINI-REVIEW - VASZILCSIN, Nicolae; DUCA, Delia-Andrada; FLUERAŞ, Adriana; DAN, Mircea-Laurenţiu (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Inhibitors of electrochemical processes have useful applications in corrosion protection of metals and alloys, as well as in galvanotechnics as levellers for the cathodic metal deposition. Active substances of drugs are good inhibitors, taking into account that they have in their molecules structures containing p electrons or lone pair electrons, being able to adsorb on the metal surfaces through weak physical or strong chemical interactions. Significant inhibition efficiency of several drugs have been proved many years ago, but unfortunately, drugs are expensive and their practical applications as corrosion inhibitors for metal and alloys has been delayed. In the present papers, the studies on the inhibition properties in metal corrosion processes of expired drugs have been emphasized, starting with the paper of R. S. Abdel Hameed, published in 2009. There are few studies on the expired drugs used as levellers in the cathodic metal deposition.